FROM OBJECT AND SUBJECT. SLAVERY, LEGAL CAPACITY AND THE BLURRING OF SERVITUDE IN LATE COLONIAL CHILE. - San Martín Aedo, William (Revista de Historia Social y de las Mentalidades, 2014)
Historians and social scientist have debated  for several decades the understanding of  black slavery in Latin America in terms  of property and primarily defined by a  dichotomic idea of “object” and “subject”.  Following this debate, I further study  combined legal and social aspects of slavery  in late colonial Chile. This perspective  demonstrates how legal rights and social  practices were superimposed over definitions  that understood slaves primarily as property.  I argue that these notions and practices  shaped an ambiguous social and legal entity,  and challenged the internal borders of their  objectuality and the relative limits of slavery.  The analysis of slave litigation at the end  of the 18th century in Chile reveals cultural  and social practices that would question the  idea of African descendants as an isolated  group mainly defined by their legal status.  Slaves and their relatives used their legal  capacity being active agents within the  judicial system. They displayed their ability  to negotiate their status within the colonial  state, and also they revealed their racially  and socially diverse support networks. The  study of these documents makes evident an  intricate system of social and legal statuses  as well as the process by which black  slaves disappeared into a broader notion of  servitude in late colonial Chile.
Keywords: Slavery; legal capacity; interethnic relationships; servitude; Chile; 18th and 19th century